Precarious inscriptions: Israel, Patagonia and the extended present in Ivo Aichenbaum´s La parte automática - Kantor, Débora Galia (Nawi, 2021)
In the argentine cinema of the last decade, and specifically in what we may consider variations of the “film-essay”, a noteworthy corpus of film, expressive of a variety of aesthetic forms and critical perspectives, has been devoted to the portrayal of Israel as a compelling territory, the territory of a particular encounter between subject, experience and “image”. “What binds me to this foreign and remote community?” This interrogation, that marked previous generations of argentine Jews, returns in each film and opens up new aesthetic and political dimensions. This article explores different aspects of Ivo Aichenbaum´s La parte automática (2012), the first in a constellation of film that we haven´t yet seen the last of.